História demográfica e o papel da paisagem na diversidade genética de Eugenia dysenterica (Myrtaceae) - Lima, Jacqueline de Souza (2015)
Eugenia dysenterica is a plant species from Cerrado that is widely distributed throughout the biome. Previous studies showed that natural populations of species have a high genetic structure, suggesting that historical changes in the geographic distribution and habitat fragmentation may have affected its genetic differentiation. In this context, studies of phylogeographic and landscape genetics are needed to understand which factors influence the distribution of genetic diversity of the species. In the first chapter we used the statistical phylogeography integrated to modeling analysis to reconstruct the demographic history and dispersal routes of E. dysenterica lineages and investigated the Quaternary climate change effects on its spatial pattern of genetic diversity. In the second chapter, we evaluated if habitat loss and fragmentation affect genetic diversity and connectivity in the species. Our results suggest that the central region of the Cerrado biome is probably the center of distribution of E. dysenterica and the spatial pattern of its genetic diversity may be the outcome of population stability through periods of the Quaternary. Moreover, also indicate that habitat fragmentation may be related to the increase in differentiation and a decrease of genetic diversity in these populations.